The Challenges of Environmental Law Enforcement to Implement SDGs in Indonesia - Salim, Agus; Palullungan, Liberthin (International Journal of Criminology and Sociology, 2021)
The 1945 Constitution of the Republic of Indonesia mandates that a good and healthy environment is a human right and constitutional right for every Indonesian citizen. Therefore, the state, government, and all stakeholders must protect and manage the environment to implement sustainable development. The Indonesian environment can remain a source and support for the Indonesian people; this is in line with implementing the SDGs. The study aims to analyze environmental law enforcement efforts in Indonesia towards SDGs implementation. The research method used a normative approach, with statutory and a conceptual process. The data collect the use of secondary data with literature and statue approach. The study results showed that environmental law enforcement in Indonesia (Number 32/2009) concerning Environmental Protection and Management is preventive and repressive. Three legal instruments in environmental law enforcement are recognized administrative, civil, and criminal law. Environmental law enforcement and the implementation of SDGs in Indonesia are connected. The government implements preventive and repressive law enforcement as regulated in Law by granting expansive powers to local governments to provide protection and environmental management in their respective regions so that the environment remains sustainable. The regulation is in line with the Goals of 6, 7, 12, 13, 14, and 15 of the SDGs directly related to environmental sustainability.